PERPANJANGAN KREDIT OLEH DEBITUR TANPA SEPENGETAHUAN PIHAK KETIGA SEBAGAI PEMBERI JAMINAN HAK TANGGUNGAN (STUDI PUTUSAN PENGADILAN NEGERI MEULABOH NO.09/PDT.G/2010/PN MBO) - FAIZAH FAIZAH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Tan Kamello3. Utary Maharany Barus Credit contract is a principal agreement while a contract on collateral is an accesoir contract which follows a principal contract or credit contract. The implementation of credit contract with collateral owned by the third party has its own regulation so that it is legal and final and conclusive. The research used juridical normative method. The nature of the research used descriptive analytic method. The result of the research showed that the legal position of the third party as the giver of the collateral in credit renewal between the Bank as creditor and the client as debtor has the same right as the debtor when the process of burdening collateral is done according to the prevailing law.. The legal consideration of the Panel of Judges in the Meulaboh District Court which state that debtor B as the defendant I has committed illegal act by not informing the implementation of the contract on collateral to the Third Party, TD, as the owner of the collateral. Therefore, SKMHT and APHT deeds becomes legally defective ad does not have any binding legal force for the parties and the Third Party.Keywords: Credit Renewal, Collateral, Third Party